Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
The paper discusses the cures available for the economic malaise that can arise because nominal interest rates cannot be reduced below zero. However, a sufficiently high rate of target inflation can prevent the occurrence. The paper highlights a number of important issues in understanding the transmission of shocks between Japan and the Asia-Pacific region. Structural reforms, information technology, and medium-term growth prospects in Japan have been discussed. The paper traced some of the links between land prices and the financial sector, and economic activity.